Do plant-growth promoting bacteria contribute to greater persistence of tropical pastures in water deficit? - A review (Research, Society and Development, 2020)
The use of plant-growth promoting bacteria (PGPB) in pastures is a sustainable alternative to increment forage production. Besides, it is an innovative technology that can mitigate the effects of water deficit (WD) in pastures. Currently, WD is one of the main abiotic stressor agents responsible for a negative impact on agricultural production. Permanent or temporary WD imposes limitations on the growth and development of forage plants more than any other environmental factors. Although there have been studies for many years to improve resistance to WD and efficiency in water usage, the mechanism involved in the process is still not clear. A better understanding of the relations between plant and water and the mechanisms of tolerance to WD can significantly improve pastures productivity and environmental quality. Despite the mechanisms that allow plants to adjust as a response to WD, depending on its severity and duration plants are not capable to survive the stress by themselves. For that reason, the use of technologies such as PGPB can make them more resistant to WD without jeopardizing their development and productivity. There are studies that show the positive effects of PGPB in grasses during WD. In this review, we are going to present an overview of the causes, effects and responses of the inoculation of PGPB in grasses exposed to water deficit.